Can African Feet Divorce Western Shoes? The Case of 'Ubuntu' and Democratic Good Governance in Malawi - Richard Tambulasi; Happy Kayuni (Nordic Journal of African Studies, 2005)
The paper points out that the concept of ‘ubuntu’, despite variations in interpretations is manifested in modern African societies. Being an African concept in orientation, some African public officers perceive it to be all encompassing and its pursuance is viewed as an empowerment to pay less attention to the ‘Western’ derived principles of democracy and good governance. Taking Malawi as a case study, the paper argues that when public officers undermine the values and principles of ‘ubuntu’ (as was the case with the government led by the Malawi Congress Party) the government becomes tyrannical and oppressive. On the other hand, pursuing ‘ubuntu’ divorced of the principles of democracy and good governance (as is the case with the current government led by the United Democratic Front), the government is prone to serious unfavourable consequences. The paper suggests that both, ‘ubuntu’ and principles of democratic good governance are compatible and complementary.